Evaluating the challenge of China's crossverging young “Enviro‐Materialists” - Anita Zhao (Journal of Consumer Behaviour, 2021)
China’s industrialisation is reshaping its younger age-generation towards increased materialism and social visibility. This is problematic because materialistic social status consumption can undermine a deeper commitment to sustainability. We evaluate this phenomenon by examining sustainable consumption buying in China, through the theories of crossvergence (valuing modernisation) and stickiness (valuing traditions). Specifically, we examine the moderation effects of Chinese age-generations, in three socio-historical periods, on this sustainability behaviour. Namely, the post-50/60s consolidation, post-70s revolution, and post-80s social reform age-generations. Utilising an online panel survey (n=981), we investigated the direct and indirect effects - via pro-environmental self-identity - of materialism, social consumption motivation, and environmental concern on these generations sustainable buying behaviours. Importantly, we found the positive direct effect of materialism on sustainability buying was significantly higher for the younger post-80s cohort, in contrast to the post-50/60s and post-70s generations. Social consumption was higher among the post-80s and post-70s generations. Environmental concern was insignificant for the post-80s, but a significantly higher influence on the post-70s generation. This suggests a new younger consumer generation is emerging, who in juxtaposition to current notions of consuming sustainably, appear to mix materialism and sustainability together to consume as green materialists. We have named this consumer group ‘enviro-materialists’. These enviro-materialists raise important questions about the currently under-researched generational underpinnings of sustainable consumption, and the macro systems within which this takes place. We propose interconnected governmental and corporate marketing interventions. These have potential to increase the sustainability behaviours of China’s enviro-materialists, whilst reducing their materialism.